2015
DOI: 10.1002/etc.3000
|View full text |Cite
|
Sign up to set email alerts
|

Assessing toxicity of copper nanoparticles across five cladoceran species

Abstract: As a result of ever increasing applications, nanoparticles will eventually end up in the environment. However, currently no common principle has been established to help understand the toxicity of nanoparticles (NPs) across species. Therefore, it is difficult to estimate the potential risks of nanoparticles to untested species in the environment. The authors exposed 4 different sizes of copper nanoparticles (CuNPs) and 1 submicron-sized copper particle to 5 cladoceran species (Daphnia magna, Daphnia pulex, Dap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
20
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 24 publications
4
20
1
Order By: Relevance
“…This variation in species sensitivity may be inversely correlated with their body size (D. magna: D. pulex: C. dubia e 4.5:3:1 approximately) and therefore body volume. This is in line with previous studies comparing chemical toxicity of species with different body sizes, reporting the inverse correlation of sensitivity with body volume to copper nanoparticles, zinc, and microplastics (Song et al, 2015;Vesela and Vijverberg, 2007;Jaikumar et al, 2018). The metabolic rates of smaller sized species are higher than that of larger species (Vesela and Vijverberg, 2007).…”
Section: Discussionsupporting
confidence: 92%
“…This variation in species sensitivity may be inversely correlated with their body size (D. magna: D. pulex: C. dubia e 4.5:3:1 approximately) and therefore body volume. This is in line with previous studies comparing chemical toxicity of species with different body sizes, reporting the inverse correlation of sensitivity with body volume to copper nanoparticles, zinc, and microplastics (Song et al, 2015;Vesela and Vijverberg, 2007;Jaikumar et al, 2018). The metabolic rates of smaller sized species are higher than that of larger species (Vesela and Vijverberg, 2007).…”
Section: Discussionsupporting
confidence: 92%
“…Small‐bodied cladocerans tend to be vulnerable to anthropogenic chemicals such as insecticides (fipronil) and copper nanoparticles (e.g., Hayasaka, Korenaga, Suzuki, Sánchez‐Bayo, & Goka, ; Song, Vijver, de Snoo, & Peijnenburg, ), which coincides with our findings for leaf extracts (Table ). The average body length of the neonate D. magna (0.90 mm) was approximately three times greater than that of S. kingi (0.28 mm).…”
Section: Discussionsupporting
confidence: 89%
“…As energy demands and usage increase with body size (Goulden et al, 1982), the effect of starvation may be magnified for the larger species at elevated temperatures (where metabolic rates are enhanced). Furthermore, a similar study comparing the sensitivity of five Cladoceran species to copper nanoparticles (Song et al, 2015) also reported that D. magna and D. pulex were less sensitive than C. dubia during acute exposures at 20 C. Similarly, a study assessing the acute toxicity of silver nitrate reported that C. dubia was more sensitive than D. magna during 48-h assays in the absence of food (Naddy et al, 2011). These observations confirm that species sensitivities have variable trends and may differ for different compounds, underlining the need for multiple species comparisons during environmental risk assessment of toxicants.…”
Section: Discussionmentioning
confidence: 99%
“…However, no studies so far have directly compared the species sensitivity of freshwater zooplanktonic organisms to microplastics. This is of importance as studies with other contaminants, including nanomaterials, have shown marked differences in sensitivity across species (Naddy et al, 2011;V€ olker et al, 2013;Song et al, 2015). Although there is not a lot of evidence for acute effects due to microplastic exposure under standardized laboratory conditions (Rehse et al, 2016), the inclusion of additional stressors may influence toxic effects observed (Heugens et al, 2001).…”
Section: Introductionmentioning
confidence: 99%